EFEKTIVITAS PERAN BALAI PENYULUH PERTANIAN TERHADAP PRODUKSI PADI KECAMATAN SIABU KABUPATEN MANDAILING NATAL - Yoyon, Yoyon Safrianto (Jurnal Publikasi Manajemen Informatika, 2022)
This study aims to determine the effectiveness of the role of Agricultural Extension on increasing rice production in Siabu District, Mandailing Natal Regency. This study uses descriptive qualitative methods with data collection techniques, namely interviews, observation and documentation. This research was conducted from January to April 2022. The results of this study explain that the rice production of farmers in Siabu District, Mandailing Natal Regency can be influenced by BPP Siabu. In addition, there are supporting and inhibiting factors in the implementation of Siabu Agricultural Extension. The role of Siabu Agricultural Extension in Mandailing Natal Regency on Siabu rice production is to increase productivity, business efficiency, income and welfare, as well as increase awareness in preserving environmental functions in order to create the vision and mission expected by BPP Siabu.